2016
DOI: 10.1021/acscatal.5b02028
|View full text |Cite
|
Sign up to set email alerts
|

PtMo Bimetallic Catalysts Synthesized by Controlled Surface Reactions for Water Gas Shift

Abstract: Supported PtMo bimetallic catalysts were prepared by controlled surface reactions (CSR) and studied for water gas shift (WGS) at 543 K. Carbon and silica supports were used for the preparation of monometallic Pt catalysts, and Mo was deposited onto these catalysts by reaction with cycloheptatriene molybdenum tricarbonyl ((C7H8)­Mo­(CO)3). Catalysts were characterized by CO chemisorption, inductively coupled plasma-atomic emission spectroscopy (ICP-AES), STEM/EDS, and XAS analysis. We report that carbon-support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 43 publications
3
27
0
1
Order By: Relevance
“…Recently reported methods for the synthesis of bimetallic nanoparticles with precise surface compositions using strong electrostatic adsorption and controlled surface reactions should further improve understanding, performance and applications of Pt–Mo catalytic structures. For comparison, the saturation limit for Mo on the surface of Pt–Mo nanoparticles prepared by controlled surface reactions was found at a Mo to Pt ratio of 0.32 based on water‐gas shift reaction testing, in line with the maximum acetic acid activity for the Pt–Mo 1/3 composition in Figure . Special properties of Pt nanoparticles decorated with Mo clusters will, therefore, be useful in the development of improved catalysts for a wide variety of reactions that require a transformation of molecules with an oxygen atom, including biomass processing, water‐gas shift, reverse water‐gas shift, deoxygenation of oxygenated aromatics, ethanol oxidation in fuel cells, and aqueous phase glycerol reforming .…”
Section: Figuresupporting
confidence: 65%
See 1 more Smart Citation
“…Recently reported methods for the synthesis of bimetallic nanoparticles with precise surface compositions using strong electrostatic adsorption and controlled surface reactions should further improve understanding, performance and applications of Pt–Mo catalytic structures. For comparison, the saturation limit for Mo on the surface of Pt–Mo nanoparticles prepared by controlled surface reactions was found at a Mo to Pt ratio of 0.32 based on water‐gas shift reaction testing, in line with the maximum acetic acid activity for the Pt–Mo 1/3 composition in Figure . Special properties of Pt nanoparticles decorated with Mo clusters will, therefore, be useful in the development of improved catalysts for a wide variety of reactions that require a transformation of molecules with an oxygen atom, including biomass processing, water‐gas shift, reverse water‐gas shift, deoxygenation of oxygenated aromatics, ethanol oxidation in fuel cells, and aqueous phase glycerol reforming .…”
Section: Figuresupporting
confidence: 65%
“…For comparison, the saturation limit for Mo on the surface of Pt–Mo nanoparticles prepared by controlled surface reactions was found at a Mo to Pt ratio of 0.32 based on water‐gas shift reaction testing, in line with the maximum acetic acid activity for the Pt–Mo 1/3 composition in Figure . Special properties of Pt nanoparticles decorated with Mo clusters will, therefore, be useful in the development of improved catalysts for a wide variety of reactions that require a transformation of molecules with an oxygen atom, including biomass processing, water‐gas shift, reverse water‐gas shift, deoxygenation of oxygenated aromatics, ethanol oxidation in fuel cells, and aqueous phase glycerol reforming . By allowing tuning of surface–oxygen interactions, Pt–Mo nanoparticles have the potential of being useful in multiple areas beyond catalysis, for example in sensing and biomedical applications.…”
Section: Figuresupporting
confidence: 65%
“…The EXAFS fitting method reported in the literature was used to differentiate Pt-Pt and Pt-Mo bonds [27,28].…”
Section: Xafs and Tem-stem Measurementsmentioning
confidence: 99%
“…It is reported that a variety of transition metals has exhibited their distinct methanation activity, such as Ni, Ru, Rh, Pd and Pt [9]. Meanwhile, another group of transition metals performs well in WGS, including Mo [10], Fe [11], Co [12], Mn [13,14] and Cr [15]. However, for the specific WGS plus methanation unit, it is necessary to develop a novel catalyst, which can simultaneously catalyze WGS and the methanation reaction.…”
Section: Co H O → Comentioning
confidence: 99%